1999
DOI: 10.1007/s004020050420
|View full text |Cite
|
Sign up to set email alerts
|

Classifying the location of osteosarcoma with reference to the epiphyseal plate helps determine the optimal skeletal resection in limb salvage procedures

Abstract: Between 1989 and 1996, 21 skeletally immature patients were treated for osteosarcoma of the extremity. Their average age was 12.6 years (range 9-16 years). We classified the location and extent of the lesion in bone on magnetic resonance imaging (MRI) with reference to the growth plate and joint margin into five subtypes. This classification served as a guide for the level of resection and the type of reconstruction required for a limb salvage procedure. All patients received neoadjuvant chemotherapy using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 1 publication
4
40
0
Order By: Relevance
“…For our series, the rate of local tumor recurrence (0%) was comparable to rates (0%-8%) reported in other studies [6,10,11] in which bone sarcomas were treated with jointpreserving resection and allograft reconstruction. This indicates joint-preserving surgery using computer navigation may be a viable and safe option for select patients with bone sarcomas.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For our series, the rate of local tumor recurrence (0%) was comparable to rates (0%-8%) reported in other studies [6,10,11] in which bone sarcomas were treated with jointpreserving resection and allograft reconstruction. This indicates joint-preserving surgery using computer navigation may be a viable and safe option for select patients with bone sarcomas.…”
Section: Discussionsupporting
confidence: 87%
“…With the advent of effective neoadjuvant chemotherapy and accurate MRI [8], a close but tumor-free margin resection is possible while sparing the juxtaarticular bone and joint as in some metaphyseal osteosarcomas around the knee [2,[9][10][11]15]. However, it is difficult to relate the tumor margins on preoperative CT and/or MR images to the actual extent of the tumor in the bone and to precisely carry out the resection in the operating room without the use of an image guidance or surgical navigation system.…”
Section: Introductionmentioning
confidence: 99%
“…Canadell et al [5] performed transepiphyseal resection in 12 high-grade osteosarcomas and had one local recurrence in their series. Our incidence of local recurrences is similar to that observed in other patients with osteosarcomas treated with limb-sparing surgery with other techniques [2,5,8,12,14]. Ferrari et al [8] reported 18 local recurrences (8%) in 230 patients who had conservative surgery.…”
Section: Discussionsupporting
confidence: 86%
“…The most common tumor resection technique used for a metaphyseal osteosarcoma of the distal femur or proximal tibia is the intraarticular resection of the distal part of the femur, proximal part of the tibia, or both [11,23]. However, intercalary tumor resection, with preservation of the epiphysis and knee, is an alternative in patients without tumor involvement of the distal part of the femur or the proximal part of the tibia [1,5,7,14,24,26]. The technique is possible in selected patients owing to advances in preoperative imaging [9,10,[18][19][20][21][22], which allows the surgeon to determine tumor margins and plan tumor resection that preserve a patient's uninvolved epiphysis.…”
Section: Introductionmentioning
confidence: 99%
“…No joint replacement can function as well as the normal knee. Recently, a few series in which the epiphysis has been salvaged have been reported [7][8][9].…”
mentioning
confidence: 99%